2016
DOI: 10.1007/s00216-016-9646-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fe3O4 nanoparticle catalyzed chemiluminescence for detection of nitric oxide in living cells

Abstract: Direct and real-time measurement of nitric oxide (NO) in biological media is very difficult due to its transient nature. Fe3O4 nanoparticles (nanoFe3O4) because of their unique catalytic activities have attracted much attention as catalysts in a variety of organic and inorganic reactions. In this work, we have developed a magnetic Fe3O4 nanoparticle-based rapid-capture system for real-time detection of cellular NO. The basic principle is that the nanoFe3O4 can catalyze the decomposition of H2O2 in the system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Synchrotron radiation (SR), because of its small beam size, low divergence, high photon flux, and linearly polarized nature, is an ideal source for the nondestructive imaging analysis. , In the last decades, synchrotron radiation have developed various powerful imaging techniques, such as microbeam XRF (μXRF), , nano and microcomputed tomography (nano and micro-CT), scanning transmission X-ray microscopy (STXM) imaging, , Fourier transform infrared (FTIR) spectroscopy imaging, etc., perform rapid, nondestructive, and label-free analysis of specimens based on principles of absorption, phase contrast, diffraction, fluorescence, etc., The synchrotron-based XRF, with a nondestructive character, can probe trace elements in biological samples with high sensitivity (sub mg·kg –1 ) and high spatial resolution (submicrometer). , FTIR microspectroscopy imaging is the technique combination of light microscopy and infrared spectroscopy, which can simultaneously provide information on structural details and molecular chemistry in samples. , The main advantage of synchrotron infrared over a traditional source is its 100–1000 times brilliance that offers operating wavelength from near-to-visible IR (wavelength >500 cm –1 ) to far-visible IR (wavelength >4000 cm –1 ) with a high signal-to-noise ratio at high spatial resolution (2–10 μm, near diffraction limit) in a short collecting time (∼minutes) . For instance, Findlay et al showed FTIR images of plaque cores (1620–1630 cm –1 ), lipid membranes (2844–2857 cm –1 ), and creatine crystals (1300–1311 cm –1 ) in a hippocampal tissue, which could provide important information in biomedicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchrotron radiation (SR), because of its small beam size, low divergence, high photon flux, and linearly polarized nature, is an ideal source for the nondestructive imaging analysis. , In the last decades, synchrotron radiation have developed various powerful imaging techniques, such as microbeam XRF (μXRF), , nano and microcomputed tomography (nano and micro-CT), scanning transmission X-ray microscopy (STXM) imaging, , Fourier transform infrared (FTIR) spectroscopy imaging, etc., perform rapid, nondestructive, and label-free analysis of specimens based on principles of absorption, phase contrast, diffraction, fluorescence, etc., The synchrotron-based XRF, with a nondestructive character, can probe trace elements in biological samples with high sensitivity (sub mg·kg –1 ) and high spatial resolution (submicrometer). , FTIR microspectroscopy imaging is the technique combination of light microscopy and infrared spectroscopy, which can simultaneously provide information on structural details and molecular chemistry in samples. , The main advantage of synchrotron infrared over a traditional source is its 100–1000 times brilliance that offers operating wavelength from near-to-visible IR (wavelength >500 cm –1 ) to far-visible IR (wavelength >4000 cm –1 ) with a high signal-to-noise ratio at high spatial resolution (2–10 μm, near diffraction limit) in a short collecting time (∼minutes) . For instance, Findlay et al showed FTIR images of plaque cores (1620–1630 cm –1 ), lipid membranes (2844–2857 cm –1 ), and creatine crystals (1300–1311 cm –1 ) in a hippocampal tissue, which could provide important information in biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…8 Synchrotron radiation (SR), because of its small beam size, low divergence, high photon flux, and linearly polarized nature, is an ideal source for the nondestructive imaging analysis. 9,10 In the last decades, synchrotron radiation have developed various powerful imaging techniques, such as microbeam XRF (μXRF), 10,11 nano and microcomputed tomography (nano and micro-CT), 12−14 scanning transmission X-ray microscopy (STXM) imaging, 15,16 Fourier transform infrared (FTIR) spectroscopy imaging, etc., perform rapid, nondestructive, and label-free analysis of specimens based on principles of absorption, phase contrast, diffraction, fluorescence, etc., The synchrotron-based XRF, with a nondestructive character, can probe trace elements in biological samples with high sensitivity (sub mg•kg −1 ) and high spatial resolution (submicrometer). 10,17 FTIR microspectroscopy imaging is the technique combination of light microscopy and infrared spectroscopy, which can simultaneously provide information on structural details and molecular chemistry in samples.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 From a medical point of view as well as an industrial perspective, the detection and determination of NO in a rapid, highly sensitive way is an important and signicant challenge. For many years, various techniques have been developed for the detection of NO, such as uorescence, 6,7 chemiluminescence, 8 electron spin resonance spectrophotometry, 9 colorimetry 10 and electrochemical methods. 11,12 Among these methods, uorescence and electrochemical techniques have become powerful tools for the investigation of this radical species.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, luminol CL systems that utilize NPs as catalysts and amplify CL signals have attracted many researchers, due to their high sensitivity or selectivity. [18][19][20][21][22] Various NPs, such as semiconductors, metals, metal oxides have proved to be effective enhancers for different CL systems and have been widely employed to detect heavy metal ions. [23] Up to now, Au NPs have been successfully employed as catalysts and have been used to detect As 3+ and Hg 2+ based on CL method.…”
Section: Introductionmentioning
confidence: 99%